Implementation of aqidah akhlak learning in improving students' discipline at mts islamiyah bindu in oku regency - Iriyansyah Iriyansyah; Ita Mawarni; Jajang Rustandi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to describe the implementation of Aqidah Akhlak learning in forming students' discipline attitudes at MTs Islamiyah Bindu, OKU Regency. The research approach used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that Aqidah Akhlak learning is carried out contextually by integrating the values of faith and morals into students' daily lives. Teachers act as facilitators and role models in instilling discipline values through reflective and experience-based learning methods. Changes in students' discipline behavior can be seen from increased compliance with madrasah regulations, time discipline, and responsibility for tasks. Supporting factors for the success of this implementation include teacher role models, school religious culture, and the habituation of religious activities. However, external challenges such as the influence of the family environment and digital media become obstacles in strengthening the values taught. In conclusion, Aqidah Akhlak learning is effective in forming student discipline if supported by a conducive learning environment and the involvement of various parties.